A Cross-Sectional Evaluation of Student Achievement Using Standardized and Performance-Based Tests. (January 2014) - Pinter, Brad; Matchock, Robert L.; Charles, Eric P.; Balch, William R.
Three groups of undergraduates (42 senior graduating psychology majors, 27 first-year premajors taking introductory psychology, and 24 first-year, high-performing nonmajors taking introductory psychology) completed the Psychology Major Field Test (MFT) and a short-answer (SA) essay test on reasoning about core knowledge in psychology. Graduating majors significantly outperformed both first-year groups using raw and covariate-corrected scores (adjusted for group differences in SAT-Verbal and high school grade point average). On the MFT, graduating majors scored above the 50th percentile, whereas high-performing nonmajors and premajors scored in the 25th and 20th percentiles, respectively. On the SA test, graduating majors averaged good -to- excellent quality responses, whereas premajors and high-performing nonmajors averaged only fair -to- good quality responses. Discussion focuses on the design and implementation of value-added, academic program assessments with limited data collection resources.